Phenomenology and Sense. Husserl and Heidegger on the Discussion on the Practical Character of Existence - Herrera, Hugo Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article analyses the attempts of Edmund Husserl and Martin Heidegger to endorsethe original practical character of existence and the contributions of both philosophers in the criticismand detection of diverse effects for human life generated by the reduction of the practical sense ofexistence by positivist positions. In this context the author compares both attempts and explains certainadvantages of the heideggerian arguments in order to give answers to problems that are not solvedsatisfactorily by Husserl.
Keywords: Phenomenology; Lebenswelt; practical sense of existence